The Mobile Phone Orchestra as a Classroom: Teaching Music with Mobile Devices - Pereira, Matheus Durães da Cunha; Geraldo, Rafael Carvalho Avidago; Rocha, Gabriel Lopes; Schiavoni, Flávio Luiz (Anais do Simpósio Brasileiro de Computação Musical, 2025)
This paper presents a pedagogical proposal for music education using mobile phone orchestras as an educational environment. By integrating mobile technologies with contemporary music teaching methodologies, we explore the potential of smartphones as accessible and versatile digital instruments. The proposal is structured in three main stages: musical experiences with everyday technologies, workshops on creating digital instruments with Pure Data, MobMuPlat, and Mixxx, and the formation of a collaborative orchestra. The theoretical framework is based on the STEAM approach and the concept of Ubiquitous Music (Ubimus), emphasizing sound experimentation, creativity, and cultural inclusion as central pillars. The project was implemented with high school and university lab students, revealing pedagogical gains, technical challenges, and high participant engagement. We observed that transforming the mobile phone into a musical instrument increases access to sound practice and establishes a bridge to formal education. The project also sparked students’ interest in traditional music learning methods, demonstrating its potential as a gateway to more structured training. Finally, we discuss the technical challenges faced and future paths for applying the methodology in broader formal educational contexts.